Gene Signatures and Prognostic Values of N6-Methyladenosine Related Genes in Ovarian Cancer - Na, Zhijing; Fan, Ling; Wang, Xiuxia (Frontiers in Genetics, 2021)
N6-Methyladenosine (m6A) is one of the most prominent modification regulating RNA processing and metabolism. Increasing studies have illuminated the vital role of m6A methylation in carcinogenesis. However, little is known about the interaction between m6A-related genes and survival of ovarian cancer (OC) patients. The purpose of this study was to obtain more reliable m6A-related genes that could be used as prognostic markers of OC using bioinformatics analysis performed on the RNA-seq data of OC. Gene expression datasets of all m6A-related genes as well as corresponding clinical data were obtained from the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA) databases. We detected differential expressed m6A-related candidate genes as well as their relationship and interaction. m6A RNA methylation regulator ALKBH5 and 35 m6A-related genes are dysregulated in OC. A gene set that could be used as a potential independent prognostic risk feature was further screened including NEBL, PDGFRA, WDR91 and ZBTB4. The results of mRNA expression analysis by PCR were consistent with those of bioinformatics analysis. We applied consensus clustering analysis on the expression of the four prognostic genes and obtained four OC subgroups TM1-TM4. There were significant differences in age, stage and grade among the subgroups, and the overall survival (OS) as well as Disease-free survival (DFS) of TM2 group were shorter than those of the other three groups. Further GO and KEGG enrichment analysis indicated that these differential genes were closely related to biological processes and key signaling pathways involved in OC. In summary, our study has indicated that m6A-related genes are key factors in the progression of OC and have potential effects on the prognostic stratification of OC and the development of treatment strategies.